KOMUNIKASI PEMASARAN ARAK BALI STUDI TENTANG PROMOSI DAN PENGUATAN IDENTITAS PRODUK LOKAL DI DESA BESAN - Ni Putu Novia Kartika Wulandari (Jurnal Komunikasi, 2026)
This study examines the marketing communication of Arak Bali in Desa Besan, focusing on the integration of cultural, economic, traditional health, and Hindu ethical principles. The analysis aims to understand how producers craft message content, select communication channels, create product image, and manage interactions with customers, so that Arak Bali is recognized not merely as an alcoholic beverage, but also as a cultural, health, and culinary tourism product. Furthermore, the study emphasizes the importance of aligning marketing strategies with the concepts of purity (Śuddha), harmony (Tri Hita Karana), and Hindu ritual contexts to respect cultural norms, build a positive image, enhance competitiveness, and contribute to the welfare of the local community. The method used in this study is qualitative descriptive with a case study approach, aiming to explore in depth the marketing communication practices of Arak Bali, including message delivery, platform selection, audience interaction, and the integration of cultural and Hindu ethical values into marketing strategies. The results of the study indicate that marketing communication for Balinese arak in Besan Village faces various technical, psychological, and cultural challenges, including producers’ low level of digital literacy, limited business management capacity, and the persistence of negative public perceptions toward arak Bali. To address these challenges, an integrated marketing communication strategy has been implemented by combining verbal, non-verbal, and digital communication, supported by village social media platforms, collaboration with cultural tourism villages and local MSMEs, and institutional facilitation. This strategy emphasizes a personal approach, transparency in the production process, the strengthening of cultural and religious values, regulatory compliance, and synergy with cultural tourism, thereby enhancing consumer trust and loyalty while reinforcing the economic and cultural value of arak Bali as a sustainable flagship product of Besan Village.